P173 The deeper, the better: Histological activity defined as Nancy Index >2 predicted bad outcomes in patients with ulcerative colitis that achieved mucosal healing. (25th January 2019) - Gonzalez-Partida, I; Gonzalez-Lama, Y; Gonzalez-Lois, C; Sanchez-Yuste, R; Salas, I; Suarez, C; Calvo, M; Matallana, V; Salas, C; Vera, I
Abstract: Background: While the endoscopic remission is a well-established good prognostic factor, histological remission is a concept still to be defined, and therefore the importance of this in the evolution of patients with ulcerative colitis (UC) is still uncertain. Getting the histological remission may be the most ambitious stage. However, achieving it in patients in endoscopic remission, it probably makes the difference. The Nancy index (NI) is an index of histological activity for patients with UC. It graduates from 0 to 4; 0) without relevant histological disease, (1) chronic inflammatory infiltrate without acute inflammatory infiltrate, (2) mild acute inflammatory infiltrate, (3) moderate or severe acute inflammatory infiltrate, (4) presence of ulcers. Methods: Our objective was to identify which patients with endoscopic mucosal healing had a higher risk of endoscopic relapse according to the degree of histological activity, by designating a useful cut-off point according to NI. For this, a retrospective cohort analysis of patients with UC in deep remission (defined as subscore endoscopic of Mayo 0) was performed in which colorectal cancer screening colonoscopies were performed by taking randomised biopsies by segments. The biopsies with greater histological damage were re-evaluated retrospectively according to the NI by expert pathologists. Results: Of a total of 52 colonoscopies with their respective biopsies included in the analysis, 38 (73.1%) had an NI < 2, and 14 (26.9%) had an NI ≥ 2. The mean follow-up was 56.4 months (SD 25.8). Of the 14 biopsies with NI ≥ 2, six patients presented endoscopic activity in 44.5 months (SD 25.1) on average. In the 38 with NI < 2, 32 presented favourable evolution. All patients had at least one control colonoscopy at follow-up. In the univariate analysis, the presence of NI ≥ 2 predicted endoscopic relapse (RR = 2.7; IC 95%; 1.1–7). Conclusions: NI was useful to evaluate the degree of histological remission in patients with UC who have reached mucosal healing. An NI ≥ 2 identified those patients who were going to relapse endoscopically throughout the follow-up. The NI < 2 could be a definition of histological remission useful in clinical practice, and would allow identifying those patients with greater risk of suffering a worse evolution to adjust their treatment and follow-up in an individualised manner.